PERAMALAN DAN PENGENDALIAN PERSEDIAAN PRODUK SLIMMING HONEY DENGAN METODE JARINGAN SARAF TIRUAN BACKPROPAGATION DAN LOT SIZING DINAMIS - Elisa Yolanda Siahaan (2021)
PT. SRA is a direct selling company that sells natural products that in its sales have problems of shortage or oversupply plus limited warehouse capacity owned. The study aims to control inventory using the lot sizing silver meal method and wagner within to maximize the use of slimming honey inventory costs. The processing begins by predicting the need for slimming honey in January-April 2021 using artificial neural network (JST) method with Matlab software and algorithm used is backpropagation. In search of the best architecture obtained is to use 55 variables on the input layer, 1 hidden layer with 15 neurons and 1 output layer. The network has the smallest MSE value of 0.0001 with a regeression value of 0.9946. The forecast result per period (6 days) during January-April 2021 is 139 , 104, 70, 72, 76, 81, 144, 199, 151, 165, 867, 840, 681, 761, 470, 185, 136, 501, 112 and 498 bottles. Then the calculation of safety stock to avoid overstocking and obtained the results of 167 bottles per day. Furthermore, a comparison between the calculation of lot sizing silver meal method with wagner within and obtained wagner within as the most optimal inventory control method with an economical inventory cost of Rp 3,768,883 with 13 orders.